تحديد المخاطر في شركات المقاولات دراسة ميدانية على شركات المقاولات العاملة في سورية - ديوب, محمد; زريقا, ولاء (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تعد خطوة تحديد المخاطر الخطوة الأولى من خطوات عملية إدارة المخاطر وتبنى على أساسها كافة المراحل اللاحقة كتحليل المخاطر وتقييمها ووضع سياسات الرد المناسبة والرقابة عليها، وكلما كان تحديد المخاطر صحيحاً ودقيقاً ستزداد دقة وصحة العمليات اللاحقة لها. جاء هذا البحث انطلاقاً من أهمية هذه الخطوة بهدف استكشاف وتحديد المخاطر الرئيسة التي تواجه شركات المقاولات العاملة في سورية.تمَّ إتباع المنهج الوصفي في الدراسة استناداً إلى المشكلة والأهداف التي تسعى إلى تحقيقها، وشمل مجتمع الدراسة كافة شركات المقاولات العاملة في سورية، واستخدم الباحث استبانة مصممة خصيصاً لتحديد المخاطر في شركات المقاولات من قبل (Zou, et.al, 2006) وتمَّ تكييف أسئلتها مع البيئة السورية.تَبَيَّنَ مِنْ خلال الدراسة أنَّ المخاطر التضخمية (كلفة المواد- أجور اليد العاملة – تكاليف النقل) تُعَدُّ من المخاطر الأساسية التي تواجه شركات المقاولات العاملة في سورية، بالإضافة إلى غياب ثقافة إدارة المخاطر تعد تهديداً كبيراً لأنها تُبقي القسم الأكبر من المخاطر مجهولاً وبالتالي آثارها ونتائجها مجهولة، ولوحظ غياب ثقافة التأمين على مختلف مراحل العمل، مما يجعل الأمور حرجة للغاية عند حدوث المخاطر وحوادث العمل.أهم التوصيات التي تمَّ التوصل إليها هي:1- تُوصى شركات المقاولات العاملة في سورية بضرورة تنظيم عقود التشييد بحيث تتضمن في بنودها احتمالات ارتفاع الأسعار وإمكانية تعديل قيمة العقد إذا اقتضت الضرورة.2- ضرورة نشر ثقافة إدارة المخاطر في كافة المستويات الإدارية في شركات المقاولات العاملة في سورية بالشكل الذي يمكنها من تحديد المخاطر المحتملة التي يمكن أن تواجهها بشكل دقيق وبالتالي الاستعداد لمعالجتها. 3- توُصى شركات المقاولات بضرورة نشر ثقافة التأمين على المخاطر، الأمر الذي يمكن من مواجهة حالات كثيرة من الحوادث غير المتوقعة ويقلل من آثارها السلبية على الأهداف والشركة ككل.The risk identification is the first stage of risk management process, and all the subsequent stages (such as risk analysis, assess, response policies and control) are based on it. The more you identify risks truly and accurately will therefore increase the accuracy and validity of all subsequent stages in risk management process. On the basis of the importance of this phase this research came to explore and identify the main risks facing the construction companies operating in Syria. We follow the descriptive study in his research based on the problem of the study and the objectives it seeks to achieve. The study population included all construction companies operating in Syria. The researcher used a questionnaire specifically designed to identify risks in construction companies by (Zou, et al., 2006) and the student conditioned its questions with the Syrian environment.The findings of this study show that inflationary risks ( materials cost- hand labor wages - transportation costs) are one of the fundamental risks facing construction companies operating in Syria, in addition to the absence of risk management culture is a major threat because it keeps a bulk of the unknown risk and thus its effects and consequences are unknown, it noted the absence of insurance culture at various stages of the work, making things very critical when risks and work accidents occurs. The most important recommendations reached by the student is:1-The construction companies operating in Syria must organize construction contracts in a way that include in its provisions the possibility of higher prices and the possibility of modifying the value of the contract. 2- Risk management is an important process at all administrative levels. It can help in determining the potential risks that may be faced and handling them.